Impact of Ocean Warming and Acidification on Symbiosis Establishment and Gene Expression Profiles in Recruits of Reef Coral Acropora intermedia - Sun, Youfang; Jiang, Lei; Gong, Sanqiang; Guo, Minglan; Yuan, Xiangcheng; Zhou, Guowei; Lei, Xinming; Zhang, Yuyang; Yuan, Tao; Lian, Jiansheng; Qian, Peiyuan; Huang, Hui (Frontiers in Microbiology, 2020)
The onset of symbiosis and the early development of most broadcast spawning corals play pivotal roles in recruitment success, yet these critical early stages are threatened by multiple stressors. However, molecular mechanisms governing these critical process under ocean warming and acidification are still poorly understood. The present study investigated the interactive impact of elevated temperature (~28.0 and ~30.5 °C) and partial pressure of carbon dioxide (pCO2) (~600 and ~1,200 μatm) on early development and the gene expression patterns in juvenile Acropora intermedia over 33 d. The results showed that coral survival was > 89 % and was unaffected by high temperature, pCO2 or the combined treatment. Notably, high temperature completely arrested successful symbiosis establishment and the budding process, whereas acidification had a negligible effect. Moreover, there was a positive exponential relationship between symbiosis establishment and budding rates (y = 0.0004e6.43x, R = 0.72, P < 0.0001), which indicated the importance of symbiosis in fueling asexual budding. Compared with corals at the control temperature (28℃), those under elevated temperature preferentially harbored Durusdinium spp., despite unsuccessful symbiosis establishment. In addition, compared to the control, 351 and 153 differentially expressed genes were detected in the symbiont and coral host in response to experimental conditions, respectively. In coral host, some genes involved in nutrient transportation and tissue fluorescence were affected by high temperature. In the symbionts, a suite of genes related to cell growth, ribosomal proteins, photosynthesis, and energy production were down-regulated under high temperatures, which may have severely hampered successful cell proliferation of the endosymbionts and explain the failure of symbiosis establishment. Therefore, our results suggest that the responses of symbionts to future ocean conditions could play a vital role in shaping successful symbiosis in juvenile coral.